The usage of subgenera in mammalian taxonomy - Teta, Pablo Vicente (2019)
In this note, I discuss the advantages of the usage of subgenera as a practical taxonomic rank in mammalian taxonomy. Use of this category preserves traditional usage, reduces nomenclatural instability and avoids unnecessary change of names. Subgenera are useful to label diagnosable clades of closely related species, especially in morphologically and ecologically diverse monophyletic genera, without alteration of traditional binomial usage. Contrary to informal names such as "divisions" or "groups", subgenera are governed by the rules of the International Commission on Zoological Nomenclature (ICZN), having usage constrained (and stability promoted) by typification and priority.